Drug Repositioning: An Approach for Drug Discovery - K. Vora, Parin; R. Somani, Rakesh; H. Jain, Madhuri (Mini-Reviews in Organic Chemistry, 2016)
Validation of new molecular entities and de novo drug discovery and development are traditional approaches of drug discovery which is costly and time consuming process. Thus, drug repositioning was an alternative approach to traditional drug discovery. Drug repositioning is also known as drug re-tasking, drug rescuing, therapeutic Switching, drug recycling, drug repurposing or drug reprofiling. It is a process or strategy of developing or discovering new therapeutic uses for failed or already marketed drug candidates/biologic/pro-drugs which maximize the therapeutic value of a drug and increase the success rates. With the increase in market competition, pharmaceutical companies are developing new drugs or new therapeutic uses, from existing/old/available drugs, by applying drug repositioning strategies, on target and off target concept, approaches and methods, which are less time consuming and less costly. However, drug repositioning faces multiple challenges which includes choosing the right therapeutic area for the test drugs of interest, issues related to clinical trials such as, need to run new trials from start if the data from the clinical or preclinical trials for the original drug or product are outdated or not satisfactory. Thus, with advancement in technology these challenges can be overcome and in future drug repositioning can provide a bright scope in providing new treatment options diseases.
Keywords: drug repositioning